Exploring the Role of Literature in Improving Reading Skills: A Mixed Method - Mosleh, Nejlania -; Setiawan, Slamet; Anam, Syafi’ul; Nugroho, Him’mawan Adi; Mustofa, Ali; Abdullah, Muhaimin (English Education : English Journal for Teaching and Learning, 2025)
This research attempts to investigate the efficacy of using literary works as learning media in improving students' reading ability. This mixed-methods study involved grade IX students in a public junior high school in Gresik. Data were acquired by surveys for quantitative data utilizing questionnaires and semi-structured interviews for qualitative data. The quantitative data were analyzed using descriptive statistics whilst the qualitative data from interviews were thematically analyzed to investigate students' perspectives and experiences. Three categories were identified from the survey data: students' interest in reading, their interest in English, and their perceptions on the usage of literary works to enhance reading abilities. According to the findings, 47% of students "agree" that reading literature can help them become better readers. This study suggests that teachers can utilize literature in reading skills according to the level of age appropriateness and alignment with learning objectives